2022
DOI: 10.48550/arxiv.2205.01711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Level Crossing Rate of Fluid Antenna Systems

Abstract: Multiple-input multiple-output (MIMO) technology has significantly impacted wireless communication, by providing extraordinary performance gains. However, a minimum interantenna space constraint in MIMO systems does not allow its integration in devices with limited space. In this context, the concept of fluid antenna systems (FASs) appears to be a potent solution, where there is no such restriction. In this paper, we investigate the average level crossing rate (LCR) of such FASs. Specifically, we derive closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…They can be realized by liquid-based radiating structures [5], [6] or reconfigurable pixels [7]- [9]. Single-user fluid antenna systems have been investigated in [10]- [16] where promising performance was revealed. An overview paper which covers different aspects of fluid antenna can be found in [17].…”
Section: A Multiple Access Via Fluid Antennamentioning
confidence: 99%
“…They can be realized by liquid-based radiating structures [5], [6] or reconfigurable pixels [7]- [9]. Single-user fluid antenna systems have been investigated in [10]- [16] where promising performance was revealed. An overview paper which covers different aspects of fluid antenna can be found in [17].…”
Section: A Multiple Access Via Fluid Antennamentioning
confidence: 99%
“…Besides, the diversity gain can be translated into a significant capacity gain [29]. Recent research also studied fluid antenna systems in Nakagami channels [30], their diversity order [31] and level crossing rates [32]. Recently in [33], Khammassi et al employed a fully correlated channel model that accurately characterizes the channel correlation between any two ports in a fluid antenna and reported that the system performance is affected more by the size of the antenna than the resolution.…”
Section: Contextmentioning
confidence: 99%
“…While most efforts in fluid antenna communication systems are limited to single-user scenarios, for example, [27][28][29][30][31][32][33][34][35][36], the fact that a position-switchable fluid antenna can access the ups and downs of fading envelope of the interference can be exploited for multiple access. Specifically, a fluid antenna assisted UE is gifted with the ability to tune in to the window of opportunity in which the interference naturally disappears in a deep fade, without prior coordination nor advanced signal processing, all by a single radio frequency (RF)-chain fluid antenna switching its port to the most desirable one.…”
Section: Contextmentioning
confidence: 99%
“…One revolutionary aspect of this is that we can contemplate to have a software-controlled, position-switchable antenna that can maximize the reception performance by choosing the best position (i.e., port selection) in a predefined space. Recently, this idea has been explored for single-user systems, e.g., [13]- [17] and multiuser systems [18]- [20]. Of particular relevance to this letter is the way in which fluid antenna deals with cochannel interference in the multiuser scenarios.…”
Section: Introductionmentioning
confidence: 99%